2022
DOI: 10.3389/fgene.2022.1011350
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential regulatory long non-coding RNA-associated competing endogenous RNA axes in periplaque regions in multiple sclerosis

Abstract: Slow-burning inflammation at the lesion rim is connected to the expansion of chronic multiple sclerosis (MS) lesions. However, the underlying processes causing expansion are not clearly realized. In this context, the current study used a bioinformatics approach to identify the expression profiles and related lncRNA-associated ceRNA regulatory axes in the periplaque region in MS patients. Expression data (GSE52139) from periplaque regions in the secondary progressive MS spinal cord and controls were downloaded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 94 publications
0
1
0
Order By: Relevance
“…Wang et al reported that miR-200a-3p, suppressed in Alzheimer’s disease models, when supplemented, led to reduced cell apoptosis, diminished amyloid beta-peptides deposits, and decreased tau phosphorylation ( 47 ). This aligns with literature suggesting a protective effect conferred by the miRNA ( 48 50 ), although its deleterious impact in various cellular contexts is also documented ( 51 53 ). The differential effects of miR-200a-3p on host cells vary with respect to human papillomavirus (HPV) infection and cancer cell types ( 54 ).…”
Section: Discussionsupporting
confidence: 90%
“…Wang et al reported that miR-200a-3p, suppressed in Alzheimer’s disease models, when supplemented, led to reduced cell apoptosis, diminished amyloid beta-peptides deposits, and decreased tau phosphorylation ( 47 ). This aligns with literature suggesting a protective effect conferred by the miRNA ( 48 50 ), although its deleterious impact in various cellular contexts is also documented ( 51 53 ). The differential effects of miR-200a-3p on host cells vary with respect to human papillomavirus (HPV) infection and cancer cell types ( 54 ).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the KEGG pathway enrichment analysis revealed significant involvement in the MAPK signaling pathway, Kaposi's sarcoma-associated herpesvirus infection, human immunodeficiency virus infection, lipids and atherosclerosis, and amphetamine addiction. The findings from this study highlight complex molecular dynamics in the periplaque region, which is an area previously underexplored in the MS landscape, offering potential future therapeutic targets [126].…”
Section: Lncrnas-pathway Involvedmentioning
confidence: 79%
“…miR-145-5p, which was also found upregulated in plasma, serum, and peripheral blood mononuclear cells of MS patients ( Keller et al, 2009 ; Søndergaard et al, 2013 ), has been characterized as a pro-inflammatory [by targeting immune response limiting factors, semaphorin 3A and cytotoxic T lymphocyte associated protein 4 ( CTLA4 )] and an anti-OPC differentiation (by targeting Myrf ) microRNA, and is thus potentially supportive of MS pathogenesis ( Fayyad-Kazan et al, 2012 ; Rezaeepoor et al, 2018 ; Kornfeld et al, 2021 ). Conversely, a bioinformatic-based network established the sponging of miR-145-5p by an upregulated long non-coding RNA, taurine upregulated 1 ( TUG1 ), in the periplaque regions in MS brains, leading to the upregulation of catenin delta ( CTNND1 ), a potential MBP-interacting protein ( Smirnova et al, 2021 ; Sabaie et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%